PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VA SD NEGERI 116 PEKANBARU - Rizana Estetika; Zulkifli '; Hamizi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problems of the background for this research is the only teacher to convey the material in front of the class and the provision of training, sometimes teachers form groups based on student adjacent seat regardless of students' abilities. This resulted in the students find it difficult to hold a debriefing. STAD cooperative learning model can improve student learning outcomes VA grade Elementary School 116 Pekanbaru. Subjects in this study were students Elementary School VA 116 Pekanbaru academic year 2014/2015 the number of students 39 people. This study design using Action Research (PTK) done in two cycles, each cycle is done twice a meeting with one final replay. Which aims to increase the research graders Elementary School VA 116 Pekanbaru with fractional ordinary matter. The results showed that the application of cooperative learning model type STAD can improve students' mathematics learning outcomes VA grade Elementary School 116 Pekanbaru. At the beginning of the data base score of 63.38, then the first cycle increased to 68.97 and the second cycle increased to 91.41. Based on the above explanation can be concluded that the implementation of cooperative learning model type STAD can improve students' mathematics learning outcomes VA grade Elementary School 116 Pekanbaru.Keywords: cooperative learning STAD type, mathematics learning outcomes